1995
DOI: 10.3109/17453679508995502
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of arthroscopic meniscectomy a 13-year physical and radiographic follow-up of 43 patients under 23 years of age

Abstract: We reexamined 43 patients with stable knees at a mean of 13 years after arthroscopic meniscectomy. The patients had a maximum age of 22 years at the operation and no patient had had previous surgery on the involved knee. At the follow-up examination, no differences in range of motion, muscle strength or tibial A/P displacement were seen between the operated and the nonoperated knees and 36 patients had no problem with their knee in daily life. Radiographic changes were found in the operated knee in 20 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
2
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 24 publications
2
45
2
1
Order By: Relevance
“…In the current literature, the proposed risk factors for postoperative radiographic change have been inconsistent. While Benedetto and Rangger [5] suggest that preexisting cartilage wear is a predictor of radiographic change after partial medial meniscectomy, others suggest that cartilage wear is not relevant [11,[26][27][28]. The volume of the excised meniscus has also been correlated with the development of radiographic change [13,27].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the current literature, the proposed risk factors for postoperative radiographic change have been inconsistent. While Benedetto and Rangger [5] suggest that preexisting cartilage wear is a predictor of radiographic change after partial medial meniscectomy, others suggest that cartilage wear is not relevant [11,[26][27][28]. The volume of the excised meniscus has also been correlated with the development of radiographic change [13,27].…”
Section: Discussionmentioning
confidence: 94%
“…The shortterm results of patients treated with partial meniscectomy are excellent [3,5,23]. However, some studies have demonstrated the development of degenerative radiographic changes after partial meniscectomy [6,7,10,[26][27][28]. Due to the impractical nature of routine second-look arthroscopy and the previous limitations of conventional imaging modalities, the early effects of arthroscopic partial meniscectomy upon subchondral bone and articular cartilage have yet to be described.…”
Section: Introductionmentioning
confidence: 98%
“…14, 15,29,30 There are few long-term follow-up studies 19,31,32 and comparison is difficult since the criteria for assessment differ. As recommended by the IKDC the radiological evaluation includes the flexion posteroanterior view.…”
Section: Discussionmentioning
confidence: 99%
“…However arthroscopic meniscectomy remains the most commonly performed orthopaedic procedure in Europe and the US [3]. It is known that complete or partial meniscectomy predisposes the knee to degenerate joint disease [4][5][6][7] and therefore it would seem logical to try to preserve injured meniscal tissue by repair, reconstruction or replacement.…”
Section: Introductionmentioning
confidence: 99%